Filling and coloring effect of pearl shell powder and dye‐loaded pearl shell powder on polypropylene. Issue 18 (9th January 2019) - Ge, Liuqin; Fan, Neng; Zhou, Youzhou; Xia, Meisheng; Ye, Ying
ABSTRACT: Dye‐loaded shell powder (DPSP), as a novel filler and pigment, was fabricated from pearl shell powder (PSP) and Direct Red 28. PSP (mean diameter of 1.94 μm) and DPSP (mean diameter of 1.62 μm) were individually incorporated into polypropylene (PP), and the mechanical, crystallization, and color properties of PSP/PP and DPSP/PP composites were investigated. As compared to PSP, DPSP exhibited superior reinforcing and toughening effects on PP, due to the ameliorated filler–polymer interfacial interaction. The optimal additive amount of DPSP was determined as 10 wt %, under which the tensile strength of PP was raised from 33.17 to 35.37 MPa, flexural strength from 41.16 to 44.35 MPa, and impact strength from 3.77 to 5.98 kJ/m 2 . In comparison with PSP/PP, higher content of β‐PP phase was confirmed in DPSP/PP composites. Furthermore, uniform redness distribution was achieved in DPSP/PP specimens, demonstrating the good coloration performance of DPSP. The results indicated that DPSP can be utilized for coloration and filling modification of polymers. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47455 Abstract :